Profit taxation, R&D spending, and innovation - Andreas Lichter; Max Löffler; Ingo Eduard Isphording; Thu-Van Nguyen; Felix Poege; Sebastian Siegloch (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
We study how business taxes affect establishments' R&D activities. Relying on geocoded panel data targeting the universe of R&D-active establishments in Germany, we exploit around 7,300 changes in the local business tax rate over the period 1987-2013 for identification. Using event study techniques, we find a sizable negative and statistically significant effect of an increase in the local business tax on establishments' total R&D spending and patents filed. Zooming into the process of innovation production, we uncover substantial heterogeneity in the impact of business taxation for various R&D inputs, among establishment characteristics, and for different types of research projects.
Keywords: H25; H32; O31; O32; 330; corporate taxation; firms; R&D; innovation; patents